Globalization and the labor share in national income - Ha Thi Thanh Doan; Guanghua Wan (Asian Development Bank Institute (ADBI), 2017)
Contradicting the conventional wisdom of constant factor shares, the portion of national income accruing to labor has been trending downward in the last three decades. This decline must have contributed to rising inequality as labor income is more evenly distributed than capital income. This study contributes to the literature on income inequality by exploring the role of globalization in driving the labor share. In particular, we focus on the impacts of trade openness and foreign direct investments (FDI) on the labor share. Using country-level panel data for 1980-2010, the study finds that trade is a significant and robust determinant of labor share. Generally speaking, export depresses while import increases the labor share. The impact of FDI, however, is insignificant. These results are similar for both developed and developing countries.
Keywords: E25; F62; D63; 330; labor share; wage share; globalization; imports; exports; FDI